Polysemia as a concept to understand the encoding of sensory information - Christian Ethier; Zohreh Vaziri; Martin Deschênes (Frontiers in Neuroscience)
In this article, we explore the concept of polysemia in sensory information processing within the brain. We suggest that, just as words can have different meanings based on context, sensory inputs are interpreted differently depending on the animal’s current state and behavior. Focusing on the trigeminal sensory nuclei in rats, we highlight the role of inhibitory circuits in gating sensory information and propose that sensory signals are polysemic, with their meaning influenced by emotional, hormonal, and motivational factors.